2PN cell donation in Germany. Or: How the German Embryo Protection (Act) undermines itself - Schickl, Hannah (Bioethics, 2019)
In contrast to embryo donation, the permissibility of 2PN cell donation is highly controversial in Germany. This article is based on there being a legal loophole with respect to 2PN cell donation, which results from an inconsistency within the Embryo Protection Act on the normative status of 2PN cells. Following that thesis, the article argues that, on the basis of the normative criterion totipotency (i.e. the capacity to develop into a born human being), 2PN cells should also be considered human embryos within the meaning of the Act and thereby be protected by that Act in the same way as embryos. However, the normative assumption that 2PN cells should already be endowed with human dignity and the right to life has absurd consequences. Moreover, the consistent continuation of the Embryo Protection Act, as well as of the underlying ethical position or argumentation (i.e. the potentiality argument), leads to the even more absurd consequence of having to place every human somatic cell under the protection of human dignity and the right to life. As totipotency or the developmental potential therefore cannot delimit entities considered worthy of protection (i.e. human embryos) from entities considered not worthy of protection (i.e. 2PN cells, gametes, hESC, hiPSC and human somatic cells), it is not a suitable normative criterion. As a paradigmatic case, 2PN cell donation demonstrates that by retaining this normative criterion the now obsolete German Embryo Protection (Act) ultimately undermines itself.